Political theologies : public religions in a post-secular world - Vries, Hent de; Sullivan, Lawrence Eugene, 1949- (UPSO - Fordham University Press E-Books., 2006)
What has happened to religion in its present manifestations? Containing contributions from distinguished scholars from disciplines, such as: philosophy, political theory, anthropology, classics, and religious studies, this book seeks to address this question.